Impaired Empathy Processing in Individuals with Internet Addiction Disorder: An Event-Related Potential Study - Jiao, Can; Wang, Ting; Peng, Xiaozhe; Cui, Fang (Frontiers in Human Neuroscience, 2017)
Internet addiction disorder (IAD) is associated with deficits in social communication and avoidance of social contact. It has been hypothesized that people with IAD may have an impaired capacity for empathy. The purpose of the current study was to examine the processing of empathy for others’ pain in IADs. Event-related potentials produced in response to pictures showing others in painful and non-painful situations were recorded in 16 IAD subjects and 16 healthy controls (HCs). The N1, P2, N2, P3, and late positive potential components were compared between the two groups. Robust picture × group interactions were observed for N2 and P3. The painful pictures elicited larger N2 and P3 amplitudes than the non-painful pictures did only in the HC group but not in the IAD group. The results of this study suggest that both of the early automatic and of the later cognitive processes of pain empathy may be impaired in IADs. This study provides psychophysical evidence of empathy deficits in association with IAD. Further studies combining multidimensional measurements of empathy are needed to confirm these findings.